2018
DOI: 10.1111/1440-1681.13054
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of progranulin (PGRN) in patients with haemophilic arthropathy

Abstract: Haemophilia A and B are rarely occurring X chromosome-linked congenital coagulation disorders dominated by spontaneous joint bleedings and chronic synovitis, leading to development of haemophilic arthropathy (HA). Progranulin (PGRN) is a growth factor with anti-inflammatory and immunomodulatory properties. PGRN is an important molecule in the pathogenesis of osteoarthritis (OA) and rheumatological disorders. This study was aimed at investigating the potential role of PGRN in the mechanisms underlying the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Even with obvious infection lesions in lungs of patients enrolled in this cohort, the levels of CRP were not significantly higher in patients as compared to healthy controls, which is consistent with the result from a previous meta-analysis showing that CRP is only robustly elevated in severe/critical cases. 25 Additionally, it is known that PGRN could competitively bind to tumor necrosis factor receptor 1 (TNFR1) 26 , 27 and TNF-α/TNFR1 is implicated in activating coagulation pathways, 28 it is therefore possible that the high levels of PGRN may block TNF-α mediated inflammation and probably coagulation pathways in COVID-19. Presumably, a lack of competitive blockage of TNF-α-induced coagulatory response due to decreased levels of PGRN in patients with severe/critical COVID-19 may be one of the mechanisms connecting PGRN to the disease severity of COVID-19 as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Even with obvious infection lesions in lungs of patients enrolled in this cohort, the levels of CRP were not significantly higher in patients as compared to healthy controls, which is consistent with the result from a previous meta-analysis showing that CRP is only robustly elevated in severe/critical cases. 25 Additionally, it is known that PGRN could competitively bind to tumor necrosis factor receptor 1 (TNFR1) 26 , 27 and TNF-α/TNFR1 is implicated in activating coagulation pathways, 28 it is therefore possible that the high levels of PGRN may block TNF-α mediated inflammation and probably coagulation pathways in COVID-19. Presumably, a lack of competitive blockage of TNF-α-induced coagulatory response due to decreased levels of PGRN in patients with severe/critical COVID-19 may be one of the mechanisms connecting PGRN to the disease severity of COVID-19 as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…(b) The cause of the increasing serum PGRN levels observed in OA patients may not be due to the disease process. Kotela et al 20 have found no significant correlation between serum PGRN levels and clinical characteristics including Knee Society Score (KSS)-knee, KSS-function, and KSS-total in OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that similarly to OA and RA, patients with HA exhibit increased levels of progranulin (PGRN), a molecule known for its protective role toward TNFα catabolic effects (Kotela et al, 2018). This evidence could open future hypotheses on its potential role as a serum-maker for monitoring disease activity.…”
Section: Tnfαmentioning
confidence: 98%